2007
DOI: 10.5194/acp-7-4887-2007
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric radiative effects of an in situ measured Saharan dust plume and the role of large particles

Abstract: Abstract. This work will present aerosol size distributions measured in a Saharan dust plume between 0.9 and 12 km altitude during the ACE-2 campaign 1997. The distributions contain a significant fraction of large particles of diameters from 4 to 30 µm. Radiative transfer calculations have been performed using these data as input. Shortwave, longwave as well as total atmospheric radiative effects (AREs) of the dust plume are investigated over ocean and desert within the scope of sensitivity studies considering… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(118 citation statements)
references
References 34 publications
11
107
0
Order By: Relevance
“…8b). Along the dust plume, with AODs reaching up to 1.40, moderate concentrations (up to 0.5 × 10 −6 kg m −3 ) are simulated between 15 and 20 • N, being low (less than 0.2 × 10 −6 kg m −3 ) between 20 and 25 • N while the maximum ones (higher than 2 × 10 −6 kg m −3 ) are recorded between 25 and 35 • N. Due to the emission of LW radiation by mineral particles, dust aerosols cool the atmospheric layers (Otto et al, 2007) in which they reside, by up to 0.8 K, and increase the temperature, by up to 0.4 K, just above the dust layer. Between the bottom of the dust layer and surface, positive RADON-RADOFF temperature differences (i.e.…”
Section: A Gkikas Et Al: Direct Radiative Effects During Intense Mementioning
confidence: 94%
“…8b). Along the dust plume, with AODs reaching up to 1.40, moderate concentrations (up to 0.5 × 10 −6 kg m −3 ) are simulated between 15 and 20 • N, being low (less than 0.2 × 10 −6 kg m −3 ) between 20 and 25 • N while the maximum ones (higher than 2 × 10 −6 kg m −3 ) are recorded between 25 and 35 • N. Due to the emission of LW radiation by mineral particles, dust aerosols cool the atmospheric layers (Otto et al, 2007) in which they reside, by up to 0.8 K, and increase the temperature, by up to 0.4 K, just above the dust layer. Between the bottom of the dust layer and surface, positive RADON-RADOFF temperature differences (i.e.…”
Section: A Gkikas Et Al: Direct Radiative Effects During Intense Mementioning
confidence: 94%
“…As recently discussed, this particle fraction significantly increases the absorption of solar radiation, represented by a decreased single scattering albedo (SSA) in the visible spectral range (Otto et al, 2007;Otto et al, 2009;McConnell et al, 2010), which affects the radiative budget. The realistic determination of large particles and the absorbing properties of the dust is, hence, very important, since uncertainties in the latter may have big effects when regionally modelling scenarios of dust outbreaks over Africa: Solmon et al (2008) have shown that different cases of solar SSA result in different forcings and heating effects and, thus, cause different dynamical feedbacks, which influence regional precipitation in Northwest Africa.…”
Section: Introductionmentioning
confidence: 92%
“…Its basic features are described in previous papers (Otto et al, 2007). The following issues were revised or extended:…”
Section: The Applied Modelmentioning
confidence: 99%
See 2 more Smart Citations